Genome-Wide Transcriptional Dynamics in the Companion Bacterial Symbionts of the Glassy-Winged Sharpshooter (Cicadellidae: Homalodisca vitripennis) Reveal Differential Gene Expression in Bacteria Occupying Multiple Host Organs. Issue 9 (1st September 2017) - Bennett, Gordon M; Chong, Rebecca A
Abstract: The agricultural pest known as the glassy-winged sharpshooter (GWSS) or Homalodisca vitripennis (Hemiptera: Cicadellidae) harbors two bacterial symbionts, " Candidatus Sulcia muelleri" and " Ca . Baumannia cicadellinicola, " which provide the 10 essential amino acids (EAAs) that are limited in the host plant-sap diet. Although they differ in origin and symbiotic age, both bacteria have experienced extensive genome degradation resulting from their ancient restriction to specialized host organs (bacteriomes) that provide cellular support and ensure vertical transmission. GWSS bacteriomes are of different origins and distinctly colored red and yellow. While Sulcia occupies the yellow bacteriome, Baumannia inhabits both. Aside from genomic predictions, little is currently known about the cellular functions of these bacterial symbionts, particularly whether Baumannia in different bacteriomes perform different roles in the symbiosis. To address these questions, we conducted a replicated, strand-specific RNA-seq experiment to assay global gene expression patterns in Sulcia and Baumannia . Despite differences in genomic capabilities, the symbionts exhibit similar profiles of their most highly expressed genes, including those involved in nutrition synthesis and protein stability (chaperonins dnaK and groESL ) that likely aid impaired proteins. Baumannia populations in separate bacteriomes differentially express genes enriched in essential nutrient synthesis, including EAAs (histidine and methionine) and B vitamins (biotin and thiamine). Patterns of differential gene expression further reveal complexity in methionine synthesis. Baumannia 's capability to differentially express genes is unusual, as ancient symbionts lose the capability to independently regulate transcription. Combined with previous microscopy, our results suggest that the GWSS may rely on distinct Baumannia populations for essential nutrition and vertical transmission.